Design of specific situation estimation function using multi-robot system in military operations - Donggyu Choi; Jaeuk Baek; Chang-eun Lee (ETRI Journal, 2025)
Modern warfare, involving both conventional combat and terrorism, often occurs in urban environments. As opposed to traditional outdoor operations, urban operations rely on indoor concealment, creating many hazardous situa-tions. Operations inside buildings result in numerous hiding spots and chal-lenges, such as stairs and varying ceiling heights, which can endanger friendly forces. Effectively responding to enemy concealment and anticipating threats in such environments are critical. The development and research of small equipment for situational awareness have increased rapidly in recent years. This study proposes a framework that uses edge devices, which are widely used in current robotics, in clusters to support effective indoor military opera-tions. The framework enables real-time object location estimation and risk zone identification, even in environments in which the resources required for robot movement are limited. The proposed framework provides auxiliary and intuitive information for situational assessment during indoor military opera-tions, such as building clearing.